Accounting regulation in the European Union - Labro, Eva; Pierk, Jochen (Review of Accounting Studies, 2025)
We provide a comprehensive overview of accounting-related regulatory changes (financial accounting, auditing, tax, and other disclosures) in the 27 European Union countries and the United Kingdom since 1993 based on an extensive literature review, survey, and topic and country expert input. Across all countries and years, we find that more than 16 regulatory events occur in a typical difference-in-differences research design that includes pre- and post-periods of four years. On average 3.4 out of four accounting disciplines are affected, emphasizing the need for interdisciplinary awareness. Our accompanying website ( http://www.eu-regulations.com ) offers visual representations of these events, regulation summaries, literature links, and source documents, all by country. This work aims to (1) lower the cost for researchers, reviewers, and editors to understand the EU’s evolving regulatory landscape; (2) improve research designs by identifying concurrent regulatory events; and (3) highlight research opportunities for those studying the EU or specific member states.